Pengaruh Lama Perendaman Dingin dan Konsentrasi Bahan Pengawet Terhadap Pengawetan Kayu Bayur (Pterospermum javanicum) Menggunakan Pengawet Ekstrak Daun Mimba (Azadirachta indica): The Effect of Cold Soaking Duration and Concentration ff Preservatives on Preservation of Bayur (Pterospermum Javanicum) Using Preservative Extract Mimba Leaf (Azadirachta Indica) - patriot muslim; Febriana Tri Wulandari; Hairil Anwar (HUTAN TROPIKA, 2022)
Wood is one of the forest products needed by humans for various uses, including as construction material, crafts, furniture and so on. The solution to save the use of wood by extending the life of the wood through the wood preservation process. The wood used in this study used Bayur wood (Pterospermum javanicum Jungh.). Bayur wood is a typical type of wood from the tropics belonging to durable class IV (easy to rot) which is wood that is easily attacked by wood-destroying organisms such as subterranean termites. Bayur wood grows and develops in secondary forest, with an altitude below 1,000 mdpl (Salmayanti et al., 2013). The aim of this research is:.(1) To determine the effect of immersion time on the value of absorption, retention and penetration of bayur wood preservation. (2) To determine the effect of the concentration of neem leaf extract preservative on the absorption, retention and penetration values ​​of bayur wood preservation. (3) To determine the interaction effect of immersion time and concentration of neem leaf extract preservative on the absorption, retention and penetration values ​​of bayur wood preservation. The results of this study indicate the conclusions that can be drawn as follows: (1) The immersion time has no effect on the value of absorption, theoretical retention, actual retention, and penetration of bayur wood immersion using neem leaf extract. (2) The concentration of preservatives has no effect on the value of absorption, theoretical retention, actual retention, and penetration. (3) The interaction between the length of immersion time and the concentration of preservatives did not affect the value of absorption, theoretical retention, actual retention, and penetration.